2020
DOI: 10.3389/fenrg.2020.571704
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis and Modification of RuO2 Materials for the Oxygen Evolution Reaction

Abstract: Ion exchange method as a green synthesis route is proposed to prepare hydrous ruthenium oxide nanoparticles (H-RuO 2). Calcination of H-RuO 2 at 350°C resulted in the crystalline rutile RuO 2 nanoparticles (C-RuO 2). Treatment of H-RuO 2 with 20 vol% ammonium hydroxide solution under microwave irradiation and calcination at 350°C resulted in a highly electrocatalytic active crystalline RuO 2 nanoparticles (A-C-RuO 2). Electrocatalytic performances of H-RuO 2 , C-RuO 2 and A-C-RuO 2 for the oxygen evolution rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…These red shifts might have originated from the more crystalline nature of Co-RuO 2 as compared to the bare RuO 2 and from the size confinement effect induced by the incident phonon in the RuO 2 after the incorporation of Co ions over the RuO 2 structure as well. From the Raman analysis, it is confirmed that Co is incorporated and well polarized with the RuO 2 structure. After confirming the formation of Co-RuO 2 , field-emission scanning electron microscope (FE-SEM) analysis was carried out to know the morphological features, which revealed the aggregated nanorod-like structure of Co-RuO 2 , and the corresponding results are given in Figure a–c . Energy-dispersive spectroscopy (EDS) analysis at the FE-SEM mode was carried out to confirm the presence of all of the expected elements like Ru, Co, and O with high purity, as can be seen from the EDS spectrum in Figure S3.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These red shifts might have originated from the more crystalline nature of Co-RuO 2 as compared to the bare RuO 2 and from the size confinement effect induced by the incident phonon in the RuO 2 after the incorporation of Co ions over the RuO 2 structure as well. From the Raman analysis, it is confirmed that Co is incorporated and well polarized with the RuO 2 structure. After confirming the formation of Co-RuO 2 , field-emission scanning electron microscope (FE-SEM) analysis was carried out to know the morphological features, which revealed the aggregated nanorod-like structure of Co-RuO 2 , and the corresponding results are given in Figure a–c . Energy-dispersive spectroscopy (EDS) analysis at the FE-SEM mode was carried out to confirm the presence of all of the expected elements like Ru, Co, and O with high purity, as can be seen from the EDS spectrum in Figure S3.…”
Section: Resultsmentioning
confidence: 97%
“…The crystal structure engineering of Ru-based materials via the doping of an alien cation is a common technique for improving the catalytic activity. Generally, doping alien cations in Ru-based materials specially in the RuO 2 lattice leads to alternation of the d-band center close to the Fermi level, thereby making the catalyst surface suitable for water adsorption with optimum adsorption energy with a higher OER activity in universal pH conditions. …”
Section: Introductionmentioning
confidence: 99%
“…Table 2 compared the performance of some typical metal oxide electrocatalysts for OER in 0.5 m H 2 SO 4 widely reported in literature. [42][43][44][60][61][62][63][64] Notably, IrO x /Pt flower exhibited superior OER performance in 0.5 m H 2 SO 4 compared to other Ru-based or Ir-based catalysts, which could be attributed to Pt nanocrystal structure loading IrO x NPs.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 95%
“…Generally, the small peak locating at 530.0 eV corresponded to the crystal lattice oxygen (metal−oxygen bonds) in RuO 2 crystals. 14,48,49 Unlike the uniform assignment of the lattice oxygen around 530.0 eV, there was a little divergence in the accurate assignment of oxygen vacancies. For example, in a study, 50 the peak at the binding energy of 530.5 eV was assigned to the surface oxygen vacancies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%